Administration and Environmental Protection - Milkov, Dragan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Environmental protection is a very important task of the state. ﻿The state in this area deals in a preventative manner, and at the same time controls the application of laws and regulations. ﻿The aim of this paper is to carry out the identification of administrative bodies dealing with environmental protection at the national, provincial and local levels. ﻿ There are administrative bodies dealing directly with matters of environmental protection. ﻿On the other hand, within the scope of some administrative authorities competent in other areas as their home field, tasks and activities that have direct or indirect links to the protection of environment can be found.